New improvements of MINHO team for RoboCup Middle Size League in 2003 - Ribeiro, A. Fernando (2004)
Although this research group has started a robotic football team in 1998, MINHO team has been participating in RoboCup only since 1999. The robots were completely developed by the undergraduate team members (mechanics, hardware and software), due to budget reasons, and every year new improvements had been made. The team came to a point where new improvements would mean complete changes in the robot design, hardware and mechanics and that meant to build 4 new robot s. Being all member of an Industrial Electronics department, our main research areas consist of general electronics, computer vision/image processing, and control. In this paper, the major changes implemented are described and some results assessed.